Constitutive and activation-inducible cyclooxygenase-2 expression enhances survival of chronic lymphocytic leukemia B cells - Ryan, Elizabeth P (Clinical immunology (Orlando, Fla.), 2006)
We recently reported that activated normal human B lymphocytes express Cox-2. These findings prompted us to evaluate whether human B-CLL cells express Cox-2 and synthesize prostaglandins. In contrast to naive human B cells, B-CLL cells constitutively expressed Cox-2 protein and produced PGE2, PGF2alpha, and TXA2. Elevated Cox-2 expression was seen in a subgroup of B-CLL cells that exhibit poor prognostic factors, including unmutated variable heavy chain status and increased CD38 expression. Furthermore, stimulation of B-CLL cells with CD40 ligand plus TNFalpha increased Cox-2 levels. The role of Cox-2 in promoting B-CLL survival was investigated using nonselective and selective Cox-2 inhibitors. Significant reductions in B-CLL survival occurred following Cox-2 inhibition. These new findings support that constitutive Cox-2 expression in B-CLL cells promotes their survival and possibly their expansion in vivo. It will therefore be important to evaluate drugs that inhibit Cox-2 as potential therapeutic agents in B-CLL in vivo